West Nile virus in overwintering mosquitoes, central Europe - Rudolf, Ivo; Betášová, Lenka; Blažejová, Hana; Venclíková, Kristýna; Straková, Petra; Šebesta, Oldřich; Mendel, Jan; Bakonyi, Tamás; Schaffner, Francis; Nowotny, Norbert; Hubálek, Zdeněk (Parasites & vectors, 2017)
BACKGROUND: West Nile virus (WNV) is currently the most important mosquito-borne pathogen spreading in Europe. Data on overwintering of WNV in mosquitoes are crucial for understanding WNV circulation in Europe; nonetheless, such data were not available so far. RESULTS: A total of 28,287 hibernating mosquitoes [27,872 Culex pipiens, 73 Anopheles maculipennis (sensu lato), and 342 Culiseta annulata], caught in February or March between 2011 and 2017 in a WNV-endemic region of South Moravia, Czech Republic, were screened for the presence of WNV RNA. No WNV positive pools were found from 2011 to 2016, while lineage 2 WNV RNA was detected in three pools of Culex pipens mosquitoes collected in 2017 at two study sites. CONCLUSIONS: To the best of our knowledge, this is the first record of WNV RNA in overwintering mosquitoes in Europe. The data support the hypothesis of WNV persistence in mosquitoes throughout the winter season in Europe.
Keywords: západonilská horečka; Culiseta annulata; Overwintering; West Nile Fever; West Nile virus; Culex pipiens; Europe; hmyz - vektory; Anopheles maculipennis; Czech Republic; Evropa; Animals; lidé; ženské pohlaví; roční období; Seasons; Humans; Flavivirus; zvířata; Hibernation; Culicidae; virus západního Nilu; Insect Vectors; Female; West Nile fever